b²c²-4bc-b²-c²+1=b²c²-2bc-2bc-b²-c²+1=
=(b²c²-2bc+1)-(b²+2bc+c²)
Дальше применяем формулы сокращенного умножения а²+2ab+b²=(a+b)² и a²-2ab+b²=(a-b)²
(b²c²-2bc+1)-(b²+2bc+c²)=(bc-1)²-(b+c)²
Применяем снова формулу сокращенного умножения
а²-b²=(a-b)(a+b)
(bc-1)²-(b+c)²=(bc-1+b+c)(bc-1-b-c)
b²c²-4bc-b²-c²+1=b²c²-2bc-2bc-b²-c²+1=
=(b²c²-2bc+1)-(b²+2bc+c²)
Дальше применяем формулы сокращенного умножения а²+2ab+b²=(a+b)² и a²-2ab+b²=(a-b)²
(b²c²-2bc+1)-(b²+2bc+c²)=(bc-1)²-(b+c)²
Применяем снова формулу сокращенного умножения
а²-b²=(a-b)(a+b)
(bc-1)²-(b+c)²=(bc-1+b+c)(bc-1-b-c)